Characterization of mortars associated with the hydraulic system of roman villa Horta de Torre (Fronteira, Portugal) - Madrid, Dulce Elizabeth Valdez (2019)
Characterization of mortars associated with the hydraulic system of roman villa Horta da Torre (Fronteira, Portugal) Villa Horta da Torre is an archaeological site from the 3rd – 4th century AD located in Fronteira, Portugal. In this Roman site, water plays an important role, due to the fact that the excavated buildings are comprised of a set of structures intended to store and channel water through a series of spaces and areas. This would create the most extraordinary displays to be viewed by a selected and privileged audience. This research aimed to carry out the chemical, mineralogical and microstructural characterization of the lime mortars related to the hydraulic structures from the excavated pars urbana of the villa, in order provide evidence for the assessment of the raw materials used for their manufacture, as well as their provenance, and to establish a chronology amongst the structures. Moreover, valuable information concerning their production techniques was obtained and contrasted with the ancient recipes given by Vitruvius, which can be used for a future outlook with a view to their consolidation and repair. A multianalytical approach was performed to conduct a complete and accurate characterization. Ten samples from hydraulic structures and two additional samples with a chromatic layer were analyzed by means of Optical Microscopy (Stereozoom and Petrographic microscope), X-ray Diffraction (XRD), Variable Pressure Scanning Electron Microscopy coupled to Energy Dispersive X-ray Spectroscopy (VP-SEM-EDS), Thermogravimetric analysis (TGA-DTG), Acid attack and Granulometric analysis. Results demonstrated that the mortars analyzed present remarkable uniformity in terms of chemical, mineralogical and microstructural composition and according to their architectural purpose. There are no variations suggesting a different chronology of their manufacture, so it is assumed that they may be contemporaneous. In terms of production, it is evident that the Vitruvius rules were not followed. It can be implied that masons would have been familiarized with the ancient recipes for construction and the usefulness of ceramics, but this knowledge was always linked to their intuition and to the availability of the materials; RESUMO: Caracterização de argamassas associadas ao sistema hidráulico da villa romana Horta da Torre (Fronteira, Portugal) A villa Horta da Torre é um sítio arqueológico do século III – IV DC, localizado em Fronteira, Portugal. Nesta villa romana, a água desempenhou um papel importante dado que os edifícios são compostos por um conjunto de estruturas destinadas a armazenar e canalizar a água através de uma série de espaços e áreas, o que criaria um ambiente cénico extraordinário para mostrar a um público selecionado e privilegiado. Este estudo teve como objetivo a caracterização química e mineralógica das argamassas de cal relacionadas com as estruturas hidráulicas associadas à pars urbana da villa, a fim de fornecer evidências sobre as matérias-primas utilizadas para sua produção, bem como a sua proveniência, e para estabelecer uma cronologia entre as diferentes estruturas. Além disso, foram obtidas informações relevantes sobre as suas técnicas de produção que contrastam com as receitas antigas indicadas por Vitrúvio, que podem ser consideradas numa perspectiva futura de consolidação e reparação. Efectuou-se uma abordagem multianalítica de modo a obter uma caracterização completa. Foram analisadas dez amostras de argamassas associadas a estruturas hidráulicas e duas amostras adicionais com uma camada cromática, através de Microscopia Óptica (Stereozoom e microscópio petrográfico), Difração de raios X (XRD), Microscopia eletrónica de Varrimento com Pressão Variável, acoplado a Espectroscopia de Energia Dispersiva de raio-X (VP-MEV-EDS), análise Termogravimétrica (ATG-DTG), ataque ácido e análise granulométrica. Os resultados demonstraram que as argamassas estudadas apresentam uma notável uniformidade em termos de composição química, mineralógica e estrutural, e de acordo com seu propósito arquitetónico. Não havendo variações dentro de cada grupo funcional, o que poderia sugerir uma cronologia diferente na sua produção, assume-se que podem ser contemporâneos. Em termos de produção, é evidente que as regras Vitruvius não foram integralmente respeitadas. Os construtores estariam familiarizados com as antigas receitas romanas de construção e com a utilidade da cerâmica, mas esse conhecimento estava sempre ligado à sua intuição e à disponibilidade dos materiais.